An Assessment of the Forward‐Looking Hypothesis of the Demand for Cigarettes. (3rd September 2018) - Kaestner, Robert; Callison, Kevin
Abstract : In this article, we develop a model of the demand for cigarettes that incorporates forward‐looking behavior related to the adverse health consequences of smoking and the addictive nature of cigarettes. The model results in several testable hypotheses that we use to examine the extent to which smokers exhibit forward‐looking behavior. Results of our study are generally supportive of the notion that smokers behave in a forward‐looking manner.